Development and Outcomes of a Streamlined Outpatient Newborn Circumcision Clinic. Issue 1 (1st January 2021) - Johnson, Emilie K.; Maizels, Max; Meade, Patrick; Mitchell, Melanie A.; Rubio, Lauren; Rosoklija, Ilina
Abstract: Introduction: Abnormal penile anatomy is suspected in approximately 20% of newborns whose families desire circumcision, yet there is no clear method to refer such cases for anatomical assessment and circumcision under local anesthesia when safe. The aim of this study was to describe development, implementation and outcomes of a newborn circumcision clinic for boys where concern about anatomical circumcision suitability exists. Methods: The workflow of a pediatric urology outpatient clinic was modified and a circumcision clinic implemented. Staff educational materials and electronic medical record referral templates were created. Circumcision suitability was assessed via checklist, and suitable patients circumcised on the same day. Clinical data were reviewed to evaluate initial implementation and patient outcomes. Results: Of 833 boys evaluated from January 2014 to April 2018, 657 (79%) were suitable to circumcise, all of whom underwent a circumcision. Of those suitable 244 (37%) had normal anatomy. The remaining 413 (63%) had minor anatomical abnormalities, most commonly penoscrotal web (297/657, 45%) and penile raphe deviation (60/657, 9%). No short-term complications were noted. Most (595/657, 91%) returned for followup within 6 weeks after circumcision. Success was achieved in 593/595 boys (99.7%), and 2 boys (0.3%) required acquired buried penis repair. Of the 176 boys with anatomy unsuitable for clamp circumcision (buried penis, chordee or hypospadias), 144/176 (82%) elected for surgical reconstruction. Conclusions: Implementing a newborn circumcision clinic for boys with possible anatomical abnormalities is feasible. Most boys are circumcised safely and successfully without general anesthesia. Operative circumcision under general anesthesia is reserved for boys requiring surgical reconstruction for significant anatomical abnormalities.